A study on transforming the knowledge in design learning environment - Mohamad, Nur Aziemah; Mohamed Khaidzir, Khairul Anwar; Ibrahim, Roliana (2016)
Design learning is a paradigm where it is often being cultivated in the architectural domain. The paradigm itself is quite different from the other pedagogies .In design learning, the students need to undergo a design process to create their artifact in a certain period of time.The process itself consists of three distinct phases, which are ideation proposal, critique and iterate.The teaching and learning session in architectural design learning environment often focuses on the interactions and thus, producing communications in the studio class.During the design process, the interactions occurred can be categorized as human-artifact and human-human. While in the design process, there is a lot of knowledge in which can be expressed and applied towards the design artifact.The expression is so tacit that sometimes it is difficult for the students to transform and capture it into explicit knowledge.The knowledge transferred from the instructor to the students can act as a scaffold in creating the design artifact. Therefore, a virtual learning tool is proposed to investigate how efficient the technology can assist the transformation of tacit knowledge into explicit in design learning environment.